A ação popular (AP) no Rio Grande do Sul : 1962-1972 - Dias, Cristiane Medianeira Ávila (2011)
This thesis examines the trajectory of the Popular Action (PA) in Rio Grande do Sul between 1962 and 1972. In this study, one has aimed to examine the ideas, forms of action, tactics and strategies that the PA adopted statewide, emphasizing the links and differences in relation to the national PA. One has observed that, after its foundation in 1962, the Popular Action supported, although critically, the reformist plan of João Goulart. The Popular Action participated in the Basic Education Movement (BEM) and, together with the Brazilian Communist Party (BCP) and the so-called "Independent", created the United Front, which maintained its hegemony within the student movement up to the state civil-military coup of 1964. After the coup, the PA went through a period of splits and internal divisions, but continued to develop actions to the worker and the student movement, opting not to join the armed struggle. In 1967, the PA adopted the integrated-production policy, which determined that militants would have to work alongside peasants and workers in various regions of the country. Sending militants became more intense after the decree of the AI-5 in December 1968. In this sense, militants were sent to Rio Grande do Sul in the mid-1969 to organize the PA student and worker sector, which had suffered the effects of repression with the removal of most of its members. In addition, the PA organized a crossing militants scheme to Uruguay and Argentina that was known as "Scheme of Border." The PA actions nearly ended in 1972, when most of its members were arrested by the Department of Political and Social Order (DPSO) in Porto Alegre. This research was based on documents produced by organs of repression such as the DPSO, the Special Comission of hummary Investigation (SCSI) at UFRGS, the newspaper Correio do Povo and testimonies of militants from the organization. The theoretical framework was based on concepts like intellectual organic, hegemony,common sense, good sense and historic bloc, as developed by Antonio Gramsci. This study also considered the concepts of "memory-free", as developed by Jacques Le Goff and the definition of "ideological frontiers", as developed by Luiz Alberto Moniz Bandeira